Chronic alcohol-related myopathy: a closer look at the role of lipids - Ganjayi, Muni Swamy; Krauss, Thomas A.; Willis, Craig R. G.; Baumann, Cory W. (Frontiers in Physiology, 2024)
Chronic alcohol-related myopathy (CAM), characterized by muscle atrophy and weakness, arises from prolonged excessive ethanol (EtOH) intake. The precise mechanisms by which EtOH induces skeletal muscle atrophy are not fully understood. This article posits that the pathophysiology of CAM may be significantly influenced by how EtOH modifies lipid profiles and alters lipid composition and content in skeletal muscle. We review existing literature on lipid alterations in CAM-afflicted individuals and analogous animal models, discuss EtOH’s direct and indirect effects on skeletal muscle lipids, and present specific instances where lipids contribute to muscle atrophy. This article advocates for a novel viewpoint, suggesting that lipid dysregulation may be the principal factor in EtOH-induced muscle wasting, offering a different angle to approach CAM research and treatment strategies.